Navigating climate change, disasters and displacement in Pakistan: a case study of Rahim Yar Khan - Khalid, Sidra; Hafeez, Mohsin; Junaid, Novaira; Aeman, Hafsa (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
Pakistan faces a multitude of environmental, social, and economic challenges that threaten its stability and development. Climate change has intensified natural hazards, such as floods, droughts, and heatwaves, which strain limited resources, disrupt livelihoods, and displace millions—compounded further by rapid population growth, urbanization, and pressure on food, land, and water systems (FLWS). Marginalized groups, including women, children, the elderly, and people with disabilities, are especially vulnerable amidst weak disaster management, inefficient governance, and inadequate infrastructure. In light of these challenges, adopting anticipatory action (AA) measures that proactively address climate-related risks is critical. Under the CGIAR Initiative on Fragility, Conflict and Migration (FCM), the International Water Management Institute (IWMI) in Pakistan conducted a comprehensive research case study in Rahim Yar Khan (RYK), a disaster-prone district (and host community to internally displaced persons (IDPs) and migrants from neighboring areas) in the Punjab province of Pakistan, focusing on the 2022 floods to evaluate the vulnerabilities of climate-displaced households, assess the impacts on FLWS, and propose strategies to improve disaster resilience. The study included a detailed survey covering the themes of livelihoods, water and food insecurity, migration challenges, water, sanitation and hygiene (WASH), menstrual hygiene management (MHM), and pre- and post- migration changes in wealth. The survey was supplemented with focus group discussions (FGDs) and key informant Interviews (KIIs) with relevant disaster management government, academia and humanitarian actors working on the ground.